A Parallel Randomized Algorithm for Finding a Maximal Independent Set in a Linear Hypergraph - Łuczak, Tomasz; Szymańska, Edyta (Journal of algorithms, 1997)
We present a randomized parallel algorithm with polylogarithmic expected running time for finding a maximal independent set in a linear hypergraph.